Development of Medical Record Technology and Information Systems on the Performance of RSU Pacitan Employees - sutanto, warkim; Arini, Merita (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
The development of Electronic Medical Record (RME) technology and information systems is an important need in the health sector to improve operational efficiency and service quality. This research analyzes the effect of implementing RME, technology user training, IT infrastructure, and data security and privacy on the performance of RSU Pacitan employees. Using quantitative methods with a cross-sectional design, data was collected from 30 respondents via a Google Form questionnaire and analyzed using SPSS. The results show that the four variables have a significant effect on employee performance (R² = 0.878), with the implementation of RME (coefficient 0.232) making administrative services easier, technology training (0.722) increasing employee self-confidence, and IT infrastructure (0.339) supporting productivity. Meanwhile, data security and privacy (-0.376) have a moderate influence because they play a more significant role in creating a safe work environment. This research confirms the importance of implementing EMR in supporting employee performance and recommends further research to analyze other aspects of EMR, as well as becoming the basis for hospital digital transformation policies.